(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The descriptive-correlation study design used to investigate the relation between parenting styles and children’s behavior difficulties by using the Parenting Styles and Dimensions Questionnaire, and Strengths and Difficulties Questionnaire to achieve study objectives. An online questionnaire applied as a method of data collecting on 101 parents (majority of them mothers) and their 4-11 years old children, 58 of them were males and 43 were females. The finding of the current study reveals that the authoritative parenting style was used more than other styles and correlated significantly with good child behaviors while the authoritarian and permissive style used less and correlated negatively with child’s behaviors. In conclusion, when parents use an authoritative or democratic style enhances children’s positive behaviors more than other styles.